Using intervention mapping to evaluate ‘High-Alert,’ a brief smartphone intervention to reduce youth cannabis-impaired driving - Robert Colonna; Patricia Tucker; Angela Mandich; Liliana Alvarez (PLoS ONE, 2025)
Youth driving under the influence of cannabis (DUIC) is a growing public health concern. While brief smartphone interventions have shown promise in reducing substance use and alcohol-impaired driving among youth, their efficacy for DUIC remains limited. Using the six-step Intervention Mapping framework, we developed and tested High Alert, a digital smartphone intervention designed to reduce DUIC among high-risk Canadian youth. The intervention was previously tested in a pilot randomized controlled trial comparing High Alert to an active control (exposure to six DUIC infographics) and a passive control (no contact). This study presents a comprehensive evaluation of High Alert using Step 6 of the Intervention Mapping framework. Reporting on this evaluation serves as a practical guide for researchers utilizing Intervention Mapping, offering valuable insights into High Alert’s formative, process, outcome, and acceptability evaluations to enhance DUIC prevention efforts. Formative and acceptability evaluations revealed High Alert’s positive reception among youth, with most participants willing to engage with it and recommend it to their peers. The program received high ratings for content and delivery, surpassing the static infographics used in the active control. Outcome evaluations demonstrated preliminary efficacy in reducing DUIC behaviour, particularly driving after cannabis co-use, compared to the no-contact group. Process evaluations highlighted implementation challenges, including online study bot activity, recruitment barriers (e.g., participant skepticism, limited ad targeting options), high attrition rates, and low adherence. Findings highlight the importance of Step 6 in Intervention Mapping, emphasizing the need for transparent and rigorous evaluation to inform future interventions. Addressing recruitment and implementation challenges is essential for improving the scalability and effectiveness of interventions targeting high-risk behaviours such as DUIC and will inform High Alert’s future testing.